(3OQGSI GdCShGb (B:s (3JbfjGJ hfeGPL (B/s - (3eSZhfj, efis; (3GdCRgQ, YRgs ((3GdCQOf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B;(3GdOGQ GdLRGFQjI(B, s, 2020)
(3GdcJGH GdMGdj jJMOK Yf efgGL OQGSI GdCShGb cCMO Cge eLGd ef eLGdGJ HMhK GdJShjb(B. (3MjK jbJQM eLehYI ef GdGLQGAGJ GdJbfjI GdJj jecf JfaPgG dGfJGL hJbOje eYdheGJ egeI hehKhbI (B. (3HgOa GdeSGYOI Ydi GJNGP GdbQGQ aj ejGOjf GdJShjb(B. (3gPg GdeYdheGJ jecf Gf JSJYed aj JMdjd eTcd Gh GbJQGM YOO ef GdMdhd Gh aj eQGLYI aYGdjI GdbQGQGJ GdeJNPI(B. (3jYO gPG GdcJGH eQLYG GSGSjG aj eLGd GdJShjb hJWHjbGJg heUOQG deYQaI JbfjGJ hWQb OQGSI GdShb, agh cJGH GcGOjej HjOGZhLjG dZGjI efg JSgjd egeI GdJOQjS (B. (3ceG jYJHQ eUOQG deSDhdj GdefXeI aj GNJjGQ GdWQb GdJbfjI GdGcKQ edGFeI ef MjK GdeOI hGdJcdaI hGdaYGdjI hGdcaGAI dMUhd Ydi GdeYdheGJ PGJ fhYjI GdLjOI dGSJZdGdgG HGdWQjbI GdefGSHI aj eLGd GdfTGW GdJShjbj(B.s
(3GdeQGLY U(B.211s
Keywords: (3GOGQI GdJShjbs; (3HMhK GdJShjbs